Mechanical Strength and Characteristics of Spent Foundry Admixed Concrete - Augustine Uchechukwu Elinwa (Journal of Building Materials and Structures, 2025)
This work is on the experimental study of the effects of spent foundry sand (SFS) and gum Arabic (GA) on concrete properties using a concrete mix proportion of 1: 1.7: 2.6 and a cement content of 357 kg/m3, water-cement (w/c) ratio of 0.5, and a GA dosage of 0.5 %. Six (6) levels of SFS replacements of 10 to 50 % were used and compared with the control concrete containing no SFS with and without 0.5 % GA. Analysis on the mechanical strength was performed using Minitab 18 Software. Also investigated were the hydration products using the XRD and SEM methods of analysis on the crushed concrete samples at the maximum strength (10 %). Some of the results of the investigation are that SFS and GA are compatible and can produce good quality concrete based on the statistical, XRD and SEM analysis. The dominant mineral oxides are CA, Si, Ag, Fe, C, K and Al with a very strong presence of Ca for concrete samples with both SFS and GA. These mineral oxides may have played substantial roles in the modification of the concrete samples.